The Antioxidant Status and Concentrations of Coenzyme Q10 and Vitamin E in Metabolic Syndrome - Chi-Hua Yen; Nae-Cherng Yang; Bor-Jen Lee; Jui-Yuan Lin; Simon Hsia; Ping-Ting Lin (The Scientific World Journal)
The purpose of this study was to investigate the levels of coenzyme Q10 and vitamin E and the antioxidant status in subjects with metabolic syndrome (MS). Subjects with MS (n=72) were included according to the criteria for MS. The non-MS group (n=105) was comprised of healthy individuals with normal blood biochemical values. The plasma coenzyme Q10, vitamin E concentrations, lipid profiles, and antioxidant enzymes levels (catalase, superoxide dismutase, and glutathione peroxidase) were measured. The subjects with MS had significantly higher concentrations of plasma coenzyme Q10 and vitamin E than those in the non-MS group, but these differences were not significant after being normalized for triglyceride level. The levels of antioxidant enzymes were significantly lower in the MS group than in the non-MS group. The subjects with the higher antioxidant enzymes activities had significant reductions in the risk of MS (P<0.01) after being adjusted for coenzyme Q10 and vitamin E. In conclusion, the subjects with MS might be under higher oxidative stress resulting in low levels of antioxidant enzyme activities. A higher level of antioxidant enzymes activities was significantly associated with a reduction in the risk of MS independent of the levels of coenzyme Q10 and vitamin E.